Mattering And Satisfaction with Life: Gender and Age Differences Among Kenyan Secondary School Students - Paul Mbatia Kihia; Anthony Muriith Ireri; Cecilia Nyambura Mwangi; James Njuguna Njoroge (Indonesian Counselor Association (IKI), 2024)
This study examined how mattering related with satisfaction with school life among secondary school students in Kenya (N= 446, M = 17.40, SD = 1.22; 55.8 % Male). Age and gender differences were also explored. Mattering had a moderate correlation with school life satisfaction. Both age and mattering explained 11 % variance in satisfaction with school life. Age and gender did not moderate the prediction of satisfaction with school life by mattering. The relationship was similar for middle and late adolescent students, but prediction was only significant among the middle adolescent group. No significant gender differences were reported among the study variables. The findings suggest that when students feel important and when their age is taken into account, they are more likely to have higher levels of satisfaction with their school experience.